2019
DOI: 10.3847/1538-4357/aaf1a8
|View full text |Cite
|
Sign up to set email alerts
|

Ocean Dynamics and the Inner Edge of the Habitable Zone for Tidally Locked Terrestrial Planets

Abstract: Recent studies have shown that ocean dynamics can have a significant warming effect on the permanent night sides of 1:1 tidally locked terrestrial exoplanets with Earth-like atmospheres and oceans in the middle of the habitable zone. However, the impact of ocean dynamics on the habitable zones boundaries (in-

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 76 publications
2
74
0
Order By: Relevance
“…All the experiments are started from an ice-free state. Tests showed that the final equilibrium states do not depend on the initial state 83 . For tidally locked planets, there is nearly no climate bistability or hysteresis 28 .…”
Section: Continents Can Influence the Open Ocean Area For Example Amentioning
confidence: 99%
See 2 more Smart Citations
“…All the experiments are started from an ice-free state. Tests showed that the final equilibrium states do not depend on the initial state 83 . For tidally locked planets, there is nearly no climate bistability or hysteresis 28 .…”
Section: Continents Can Influence the Open Ocean Area For Example Amentioning
confidence: 99%
“…1 except that the ratio of orbital period to rotation period is 3:2, rather than 1:1 (Supplementary Table 2 41,71 . We have modified the model to simulate the climates of tidally locked terrestrial planets in the habitable zone of low-mass stars 17,20,83,84 . The model includes four components-atmosphere, ocean, sea ice, and land, and one coupler is used to connect them.…”
Section: Continents Can Influence the Open Ocean Area For Example Amentioning
confidence: 99%
See 1 more Smart Citation
“…Such a scenario is discussed by Yang et al [2014] (see also Menou, 2013;Leconte et al, 2013;Turbet et al, 2016), but ROCKE-3D both lacks a dynamic land ice model that accounts for the glacial flow that could possibly replenish the dayside with water (to some degree) and the duration of simulation time necessary to largely evacuate the Pacific Ocean is well beyond reasonable simulation run durations. The tidally-locked/sun-synchronous 365x simulations produce familiar patterns [Yang et al, 2013;2014b;2019a;2019b;Kopparapu et al, 2017;Fauchez et al, 2019] of a very thick sub-stellar cloud, primarily composed of ice particles at high altitudes (Figure 3 ), that is not perfectly round but instead modulated by the presence of continents and a dynamical ocean transporting heat poleward.…”
Section: Simulated Climate and Atmospheric Dynamicsmentioning
confidence: 99%
“…Wordsworth et al, 2011; Abe et al, 2011; Pierrehumbert, 2011; Selsis et al, 2011; Leconte et al, 2013; Wang et al,. 2014; Yang et al, 2014a, 2014b; Shields et al, 2013, 2016; Koll & Abbot, 2015; Wordsworth et al, 2015; Pierrehumbert & Ding, 2016; Bolmont et al, 2016; Way et al, 2016, 2018; Popp et al, 2016; Wolf et al, 2017; Kopparapu et al, 2017; Turbet et al, 2016; 2017; Boutle et al, 2017; Fujii et al, 2017; HaqqMisra et al, 2018; Kodama et al, 2018; Del Genio et al, 2019; Jansen et al, 2019Yang et al, 2019a). However, the climate of planets depend on many parameters, including the total stellar irradiation, the atmospheric composition, the volatile inventory, the planetary rotation rate, the surface properties, and the presence of clouds or hazes [Forget & Leconte, 2014].…”
Section: Introductionmentioning
confidence: 99%